“Exploring Sustainable Investment Frontiers: A Bibliometric Analysis on current trends and hurdles in incorporating ESG into Investment decision-making” (Journal of Informatics Education and Research, 2024)
Integrating environmental, social, and governance (ESG) factors into investment decision-making has emerged as a critical area of interest in both academic and industry circles. This literature review aims to comprehensively explore and synthesize existing research on this topic by providing valuable insights into current trends, challenges, and prospects in sustainable investing. Articles, reports, and case studies published in relevant databases from 2019 to 2023 are reviewed for this research. A comprehensive search strategy encompassing keywords related to ESG integration in investment decisions has been used in the review process. The integration of ESG factors in investment decisions has evolved significantly in recent years. However, the knowledge landscape is scattered, and it is imperative to consolidate this body of research to gain a holistic understanding thus this bibliometric analysis addresses the research agenda on the impact of the integration of ESG factors on investment decision-making and the challenges and opportunities associated with this evolving paradigm. Our review highlighted that ESG integration has been shown to mitigate risk and enhance long-term returns, supporting the argument that sustainability considerations are not only ethical but also financially prudent. As per the analysis, hurdles range from the lack of awareness regarding standardized ESG metrics and reporting to concerns about greenwashing. The complexity of ESG factors and the need for robust data and analytics pose significant hurdles to investors and practitioners. The synthesis of findings from the study highlights the need for standardized ESG reporting, enhanced data quality, and increased stakeholder engagement. Future research should explore the integration of ESG factors in specific asset classes and regions, as well as investigate the effectiveness of various ESG integration strategies.